The Selection of Revaluation Method and The Independent Valuer Increase The Audit Fee: a case of ASEAN - Reni Setiani Sujana; Aria Farah Mita (The Indonesian Journal of Accounting Research, 2019)
Abstract: The purpose of this research is to analyze the effect of revaluation model and the use of independent appraiser on audit fees of manufacturing companies in ASEAN. This research covers five countries in ASEAN: Indonesia, Philippines, Malaysia, Singapore, and Thailand. The result of this study indicates that audit fees are higher for firms using the revaluation model compared to the cost model. Besides, audit fees are higher for firms that reporting their fixed assets at fair values appraised by internal appraiser than the independent appraiser.